Розвиток біомедичних електронних пристроїв та систем - Кондратюк, О. С. (ХНУРЕ, 2023)
Biomedical electronic devices and systems are important tools for the diagnosis, treatment, and monitoring of various human diseases. Advances in biomedical electronics technology have led to the development of more accurate and efficient medical devices and systems. Biomedical electronic devices help detect diseases at an early stage, ensure precise drug dosing, and reduce the time spent on examination and treatment. The use of biomedical electronic devices reduces the risk of errors in diagnosis and treatment, thus improving the quality of medical care. The development of the Internet of Things and wireless communication technologies enables the creation of biomedical health monitoring systems that can remotely send data to doctors and medical centers.